№1 (х+4ц 9/11) - 5 ц 6/11= 1 ц 8/11

№2 13ц 2/9 - (7 5/9 + у) = 3 ц 5/9 ПОЖАЛУЙСТА РЕШИТЕ)

1

Ответы и объяснения

2013-02-06T18:17:03+00:00

(х+4.9/11)-5.6/11=1.8/11

х+4.9/11=1.8/11+5.6/11

х+4.9/11=6.14/11

х+4.9/11=7.3/11

х=7.3/11-4.9/11

х=(7-4)+(3/11-9/11)

х=3.3-9/11

х=2.11+3-9/11

х=2.5/11

проверяем

(2.5/11+4.9/11)-5.6/11=1.8/11

13.2/9-(7.5/9+у)=3.5/9

7.5/9+у=13.2/9-3.5/9

7.5/9+у=(13-3)+(2/9-5/9)

7.5/9+у=10.2-5/9

7.5/9+у=9.9+2-5/9

7.5/9+у=9.6/9

у=9.6/9-7.5/9

у=2.1/9

проверяем

13.2/9-(7.5/9+2.1/9)=3.5/9